Brain tumor detection with convolutional neural network - Galib, Abrar Tahmid; Taposh, Maruf Hasan; Nazim, Annas Mohd. (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.